Analisis Kesesuaian Dan Daya Dukung Kawasan (DDK) Wisata Rekreasi Pantai Di Pantai Yeh Gangga, Tabanan, Bali - Kertadana, I Pande Made Lanang; Dirgayusa, I Gusti Ngurah Putra; Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences; Vol 9 No 1 (2023)DO - 10.24843/jmas.2023.v09.i01.p02, 2023)
Yeh Gangga Beach is growing tourist attraction in Tabanan Regency, Bali. Tourism activities have a close bond with natural resources owned by the tourist area. The feasibility/suitability of a tourist area and the number of visitors that can be accommodated in tourist activities is important to know, so as not to cause disruption to both tourist activities and the environment and the direction of development. This research has a purpose, namely knowing the Tourism Conformity Index and Regional Support Capacity for coastal recreation activities. The method used is purposive field observation sampling at 4 point stations and interviewing tourists by accidental random sampling. The data used is primary and secondary data, with analysis of The Tourism Conformity Index and Regional Carrying Capacity. The results of the study obtained an average area for tourism activities of 17.98 m2 and time for tourism activities for 2 hours 14 minutes per day with a value of Regional Support Capacity of 3,273 people/day, 98,190 people/month and 1,178,280 people/year. The Tourist Conformity Index shows a value of 85.11% at station 1, 86.90% at station 2, 77.97% at station 3, and 80.35% at station 4. With this area Yeh Gangga Beach is still under carrying capacity and still suitable for beach recreation activities in accordance with the utilization zone of beach recreation tourism in Yeh Gangga.